Analisis Perbandingan Metode TAM dan UTAUT Terhadap Tingkat Penerimaan Pengguna Aplikasi Easy Access - Andre, Muhammad; Damayanti, Nita Rosa; Andri, Andri; Ibadi, Taqrim (Journal of Information System Research (JOSH), 2024)
The Easy Access application is designed to facilitate employee attendance tracking, manage leave request letters, monitor employee working hours, and manage all employee personal data. However, despite these benefits, there are still issues present, such as several features that have not been optimized, including employee data fields that are empty or not available. This research is conducted to compare the TAM and UTAUT methods concerning the user acceptance level of the Easy Access application in the workplace of PT Semen Baturaja Tbk. The data analysis technique used in this study is SEM-PLS. Based on the comparison between the TAM and UTAUT methods, the hypothesis testing results indicate that all hypotheses in the TAM method are accepted, with the highest t-statistic reaching 10.257. Meanwhile, in the UTAUT method, four hypotheses are accepted with the highest t-statistic of 4.074, while one hypothesis is rejected, indicating that the social influence variable does not have a significant effect on behavioral intention, with a t-statistic of 1.554 < 1.98 and a p-value of 0.120 > 0.05. However, the UTAUT model shows an advantage in the R-square test, achieving the highest value of 56% for the user intention variable, while the TAM only reaches 49.6% for the same variable. This indicates that although the TAM model has more significant relationships between variables, the UTAUT model is better at explaining the variation in overall user acceptance of the application.